DIAGNOSTIC PERFORMANCE OF FINE NEEDLE ASPIRATION CYTOLOGY (FNAC) IN THE DIAGNOSIS OF BREAST LUMPS - Shah, Sayed Agha Ali; Pervez, Shagufta Nasir; Javed, Khalid (Journal of Ayub Medical College Abbottabad, 2013)
Objective: The aim of the study was to evaluate the diagnostic performance of fine needle aspiration cytology in the diagnosis of breast lumps. Methods: All patients who underwent FNA breast lumps at Rehman Medical Institute, Peshawar during 2006 to 2008 were included in this descriptive cross-sectional study. The FNA procedure was performed & interpreted by experienced cyto-pathologists. FNAC of 102 breast lumps were analysed. Results: The age range of the patients was 15-80 years (mean 38.11 years). Inadequate cases were 2.94%, malignant 30.39%, atypical/suspicious of malignancy 6.86%, and benign 59.80%. Malignant lesions predominated in the 5th and 6th and benign in the 3rd and 4th decades of life. Conclusion: FNAC of breast is simple, cost-effective and less traumatic method for diagnosis of breast lumps. Combined with physical examination and imaging studies, it is a highly sensitive diagnostic tool and can reduce the need for open biopsy. Keywords: FNAC, Breast lumps, Breast cancer, Breast, Diagnosis, Cytology